لأقسام التشخيصية والعلاجية للمستشفيات المعاصرة (الاشعة، المختبرات، العلاج الطبيعي ) - امجد محمود البدري; سارة ثائر جعفر (Journal of Engineering, 2015)
This research study changes in the requirements space for diagnostic and therapeutic departments (radiology, laboratory and physical therapy), which aims to adopt the current technological developments and work to create a flexible environment that helps to absorb modern technology in the future , And reach to the ideas of a new architectural flexibility to deal with those departments , And that had a major impact on the workflow in the hospital and its spaces. Through the study of modern design requirements of those departments and the study estimates for all future expansions .